Laser melting deposition of aluminium 7050 alloy: heat treatment, microstructure and mechanical properties. Issue 15 (13th October 2022) - Li, Jianan; Zhao, Hongjin; Deng, Shenghua; Liu, Xu; Ojo, Olanrewaju A.; Zhang, Lina; Li, Weirong
ABSTRACT: In this study, the microstructure and mechanical properties of laser melting deposited 7050 aluminium alloy are investigated. An anisotropic microstructure is observed in the alloy: the columnar-grained structure on the building plane and a fine equiaxial structure on the scanning plane. Pores are the main metallurgical defects found but a higher energy input can significantly reduce large pores. The mechanical properties can be significantly improved with heat treatment. After being subjected to multiple solution and aging treatments, the hardness, ultimate tensile strength and elongation at break of the printed alloy increase by 58.6%, 14.06% and 27.8%, respectively. This research offers a reference for the formation technique of large and complex 7xxx series aluminium alloy parts by additive manufacturing.